KEPEMIMPINAN TRANSFORMASIONAL KEPALA PERPUSTAKAAN DALAM MENINGKATKAN KINERJA PUSTAKAWAN DI PERPUSTAKAAN UNIVERSITAS PENDIDIKAN GANESHA - Ni Komang Natalia Pertiwi; Ketut Gede Harsana; I Putu Suhartika (D3 Perpustakaan FISIP UNUD, 2025)
This study aims to analyze how the transformational leadership of the Head Librarian enhances the performance of librarians at the Library of Ganesha University of Education. The background of the study is based on the premise that transformational leadership is considered an effective leadership model for managing change and improving the motivation and performance of librarians. This research employs a qualitative approach with a descriptive method. Data collection was carried out through direct observation and interviews at the Library of Ganesha University of Education. The findings reveal that the head librarian implements the four dimensions of transformational leadership, namely idealized influence (charisma), inspirational motivation, intellectual stimulation, and individualized consideration. This leadership approach contributes to increased productivity, adaptation to technology, and team solidarity among librarians. Other supporting factors such as a structured work system, adequate facilities, and strong teamwork also enhance the effectiveness of library services. Through a flexible and innovative leadership approach, the library is able to deliver more optimal and responsive services to meet the needs of its users.